Online Ratings of Primary Care Physicians: Comparison of Gender, Training, and Specialty. (23rd April 2021) - Wachs, Daliah; Lorah, Victoria; Boynton, Allison; Hertzler, Amanda; Nichols, Brandon; Kraft, Joseph; Wang, Jerry; Dang, Ivy; Kalekas, Paul; Vanier, Cheryl
The purpose of this study was to explore patient perceptions of primary care providers and their offices relative to their physician's philosophy (medical degree [MD] vs doctorate in osteopathic medicine [DO]), specialty (internal medicine vs family medicine), US region, and gender (male vs female). Using the Healthgrades website, the average satisfaction rating for the physician, office parameters, and wait time were collected and analyzed for 1267 physicians. We found female doctors tended to have lower ratings in the Midwest, and staff friendliness of female physicians were rated lower in the northwest. In the northeast, male and female MDs were rated more highly than DOs. Wait times varied regionally, with northeast and northwest regions having the shortest wait times. Overall satisfaction was generally high for most physicians. Regional differences in perception of a physician based on gender or degree may have roots in local culture, including proximity to a DO school, comfort with female physicians, and expectations for waiting times.